Relationship Between Stigma And Quality Of Life Among Head Of Families Who Are Undergoing Tuberculosis Treatment In Magelang Regency - Rahma Isna Saidah; Ety Rahayu (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Tuberculosis (TB) is a communicable disease that must be taken seriously because this disease can have implications on the psychological, economic, and social well-being of people with TB, which can affect their quality of life. Apart from that, phenomena in society show that there is still high TB stigma in society which can reduce the quality of life of people with TB. This study aims to determine the relationship between stigma and the quality of life among head of families who are undergoing TB treatment. This research is a cross-sectional study that was carried out on 85 heads of families who were undergoing TB treatment in Magelang Regency, Indonesia. This research was specifically carried out on a population among heads of families who were undergoing TB treatment with the consideration that the status as head of the family might cause a higher economic burden than for people with TB who do not have the status as head of the family. Data collection from respondents was carried out using a quality-of-life measurement questionnaire in the form of a 4-point Likert scale and Van Rie TB Stigma Scale for stigma measuring instruments. The results of the analysis using Kendall's Tau-b correlation showed P value=0.001 (P value<0.05) and r= -0.337, which means there is a negative relationship between stigma and quality of life. The higher the stigma, the lower the quality of life, conversely, the lower the stigma, the higher the quality of life among heads of families undergoing Tuberculosis treatment in Magelang Regency.